Membrane-Disrupting Activity of Antimicrobial Peptides and the Electrostatic Bending of Membranes - Taheri-Araghi, Sattar (University of Waterloo, 2010)
Antimicrobial peptides (AMPs) are not only fast microbe-killing molecules deployed in the host defense of living organisms but also offer valuable lessons for developing new therapeutic agents. While the mode of action of AMPs is not clearly understood yet, membrane perturbation has been recognized as a crucial step in the microbial killing mechanism of many AMPs. In this thesis, we first present a physical basis for the selective membrane-disrupting activity of cationic AMPs. To this end, we present a coarse-grained physical model that approximately captures essential molecular details such as peptide amphiphilicity and lipid composition (e.g., anionic lipids). In particular, we calculate the surface coverage of peptides embedded in the lipid headgroup-tail interface and the resulting membrane-area change, in terms of peptide and membrane parameters for varying salt concentrations. We show that the threshold peptide coverage on the membrane surface required for disruption can easily be reached for microbes, but not for the host cell -- large peptide charge (≳4) is shown to be the key ingredient for the optimal activity-selectivity of AMPs (in an ambient-salt dependent way). Intriguingly, we find that in a higher-salt environment, larger charge is required for optimal activity. Inspired by membrane softening by AMPs, we also study electrostatic modification of lipid headgroups and its effects on membrane curvature. Despite its relevance, a full theoretical description of membrane electrostatics is still lacking -- in the past, membrane bending has often been considered under a few assumptions about how bending modifies lipid arrangements and surface charges. Here, we present a unified theoretical approach to spontaneous membrane curvature, C0, in which lipid properties (e.g., packing shape) and electrostatic effects are self-consistently integrated. Our results show that C0 is sensitive to the way lipid rearrangements and divalent counterions are modeled. Interestingly, it can change its sign in the presence of divalent counterions, thus stabilizing reverse hexagonal (HII) phases.
Keywords: Antimicrobial peptides; Lipid bilayer; Bending of lipid membranes; Physics